Antibiotic usage for rotaviral diarrhea among children in Libya - Alkoshi, Salem I.; Ernst, Kacey C.; Dahlui, Maznah B. (International Journal Of Community Medicine And Public Health, 2017)
Background: In Libya, routine access to rotavirus testing is not available and clinicians treat presumptively, leading to inappropriate treatments. This study describes the management of rotavirus infection among Libyan children in public hospitals. Methods:A prospective cross-sectional study was conducted to describe the management of rotavirus among children in three public hospitals in Libya from August 2012 to April 2013. We reviewed internal documents to determine if protocols were in place to guide management of diarrheal illness. Children under five presenting with diarrhea had stool samples collected and tested for rotavirus. Comparisons of treatments were made by rotavirus status and level of dehydration; mild, moderate and severe. Results: A total of 545 diarrhea patients below 5 years of age were enrolled in the study. Of those, 311 (57%) cases were infected by rotavirus. Treatment was administered without investigating the cause of diarrhea. Intravenous fluids (IVF) treatment was the most common treatment for rotavirus cases and was administered to 306 (98%) of cases. Antibiotics were administered to about 137 (44%) of rotavirus cases. Antibiotics were more likely to be administered with more severe dehydration. Conclusions:Presumptive treatment with antibiotics was very common in Libyan. Protocols for management of diarrheal illness and rotavirus cases in children need to be established for effective treatment.